An analysis of recent trends of tuberculosis using drug sales data in a Shajapur district of Central India - Shukla, Yogesh; Yadav, Shobhana; Agarwal, Sanjay; Nayak, Anirudh (Asian Journal of Medical Sciences, 2023)
Background: There is a pressing need for systematic approaches for monitoring how much tuberculosis (TB) treatment is ongoing in the public and private sectors in India, Both to shed light on the true scale of the problem and to help monitor the progress of interventions currently being planned to address this problem. Aims and Objectives: (1) To estimate the incidence of TB in 2021 by using drug utilization data in the public and private sectors of the Shajapur district. (2) To calculate the decline in patient months from the base year 2015 to 2021; (3) To find out the recent trends and volumes (patient months) using drug sales data in the public and private sectors. Materials and Methods: Secondary data verification was done from December 2021 to March 2022 in Shajapur district, Madhya Pradesh, India. The district-level data on drug consumption in the public was obtained from the drug store records of the district TB Center and drug sales in the private sector were obtained from the DTO, which was prepared by the drug inspector in compliance with the letter of the Directorate of Health services, Madhya Pradesh, Bhopal, and CMHO Shajapur for the review of drug sale data in the private sector for subnational certification. Results: The incidence of TB increased from 113.7/lakh population in 2015 to 151.5 lakh population in 2021. The patient month of the public sector is increasing from 2015 (patient months 3653.4) to 2021 (patient months 6064.84), which indirectly denotes that more patients are taking antitubercular treatment form the government sector as compared to the private sector in the current year. The private sector sale of the drugs is decreasing from 2015 (patient months:- 9507) to 2021 (patient months: 2012.61), but still 24.91% of antitubercular drugs are provided by the private sector. Conclusion: Subnational verification of claims by Shajapur district for progress toward TB-free status in India showed that the incidence of TB is increasing from the base year to the year 2021. So it was not recommended for an award in the silver category by the verification team.